"Top-Three" health reforms in 31 high-income countries in 2018 and 2019: an expert informed overview. Issue 7 (July 2021) - Polin, Katherine; Hjortland, Maximilien; Maresso, Anna; van Ginneken, Ewout; Busse, Reinhard; Quentin, Wilm
Abstract: Background: High-income countries continuously reform their healthcare systems. Often, similar reforms are introduced concomitantly across countries. Although national policymakers would benefit from considering reform experiences abroad, exchange is limited. This paper provides an overview of health reform trends in 31 high-income countries in 2018 and 2019, i.e., before Covid-19. Methods: Information was collected from national experts from the Health Systems and Policy Monitor network. Experts were asked to report on the three "top" national health reforms 2018 and 2019. In 2019, they provided an update of 2018 reforms. Reforms were assigned to one of 11 clusters and identified as one of seven different reform types. Results: 81 reforms were reported in 28 countries in 2018. 44/81 went to four clusters: 'insurance coverage & resource generation', 'governance', 'healthcare purchasing & payment', and 'organisation of hospital care'. In 2019, 86 reforms in 30 countries were reported. 48/86 fell under 'organisation of primary & ambulatory care', 'governance', 'care coordination & specialised care', and 'organisation of hospital care'. Most 2018 reforms were reported ongoing in 2019; 27 implemented; seven abandoned. Health agency-led reforms were implemented most frequently, followed by central government-legislated reforms. Conclusions: Policymakers can leverage international experience of distinct reform approaches addressing similar challenges and similar approaches to address distinct problems. Such knowledge may help inspire or support future successful health reform processes.